Authoritarian Parenting Style: Communication Patterns Between Parents and Teenagers in The Village of Greged - Fresy Latifah Azies; Siti Khumayah; Aghnia Dian Lestari (Green Publisher Indonesia, 2026)
Communication between parents and adolescents plays a crucial role in shaping family relationships and developing adolescents’ self-concept. However, in families that practice an authoritarian parenting style, communication tends to be one-sided and lacks dialogue. This study aims to examine communication patterns between parents and adolescents in families that practice an authoritarian parenting style in Greged Village and to identify the impact of these communication patterns on adolescents. This study employs a qualitative descriptive approach. Data were collected through semi-structured interviews with parents and adolescents in families practicing an authoritarian parenting style, as well as through observation and documentation. The results indicate that the communication patterns used are directive and instructional, characterized by parental control marked by high expectations, strict supervision, somewhat rigid rules, and the use of punishment, thereby limiting adolescents’ opportunities for dialogue. On the one hand, this pattern appears to foster obedience, discipline, and a sense of responsibility in adolescents. On the other hand, strict control and high parental demands may also lead to stress, low self-confidence, and a tendency to hesitate when expressing opinions. Furthermore, the parent-child relationship is often marked by tension and emotional distance. Thus, authoritarian parenting can foster compliance in children but also risks causing psychological stress, low self-esteem, and a decline in the quality of family relationships.